2021
DOI: 10.1186/s13063-021-05856-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a periodized circuit training protocol delivered by telerehabilitation compared to face-to-face method for knee osteoarthritis: a protocol for a non-inferiority randomized controlled trial

Abstract: Background Regular exercise is an effective method for reducing pain and disability in patients with knee osteoarthritis (OA), as well as improving body composition. Thus, a combination of both resistance and aerobic training (circuit training) has shown to be promising for this population. However, access to physical therapy is limited by physical distance, social isolation, and/or treatment costs. Remote rehabilitation seems to be an effective way to minimize these barriers, but the benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The authors are also aware of a number of ongoing studies addressing a range of innovative digital programmes in OA care. Such approaches will likely receive further attention in future updates of these recommendations 78–81…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors are also aware of a number of ongoing studies addressing a range of innovative digital programmes in OA care. Such approaches will likely receive further attention in future updates of these recommendations 78–81…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches will likely receive further attention in future updates of these recommendations. [78][79][80][81] With regard to outcomes, most of the included studies reported effects primarily on pain and physical function. To follow the recommendations on prioritised outcomes in OA research, 82 more studies investigating the effects of interventions on QoL and patients' global assessment of the target joint may have provided additional relevant information.…”
Section: Research and Educational Agendasmentioning
confidence: 99%
“…The success of home-based rehabilitation programmes depends on the feasibility of the interventions and on patient adherence [23]. A previous study in which participants completed a home-based muscle strengthening and joint flexibility programme found high adherence rates (96-100%) [24].…”
Section: Of 15mentioning
confidence: 99%
“…Moreover, the selection of appropriate physical therapy content and intensity level also plays an important role in the effectiveness of physical therapy for OA (Aily et al, 2021;Wise, 2022). Therefore, more detailed and unified standards of physical therapy for OA are needed, by which clinicians or rehabilitation therapists can make personalized prescriptions according to the different situations.…”
Section: Standard and Personalized Exercise Modalitymentioning
confidence: 99%